Nanomaterial-based optical- and electrochemical-biosensors for urine glucose detection: A comprehensive review - Tian-Tian Wang; Xiao-Feng Huang; Hui Huang; Pei Luo; Lin-Sen Qing (Advanced Sensor and Energy Materials, 2022)
Urine glucose detection is an important diagnostic tool for screening and early diagnosis of diabetes mellitus. Detection of urine glucose has many advantages over blood glucose, such as non-invasive, easy-to-detect, simple sampling and being well accepted by patients. Therefore, it is commonly used to monitor diabetes progression, assist in therapeutic intervention as well as in point-of-care testing (POCT). In recent years, with the development of material science, electrochemistry and miniaturization technology, novel applications of natural enzymes, nanozymes as well as nanomaterials, such as metal (Au, Pt, Ni, Co, etc.), alloy, grapheme, in the analysis of urine glucose level have been increasing sharply. In particular, different types of nanozymes-based biosensors, inspired by natural enzymes, have been developed with improved characteristics of being low-cost, stable, and mass-produced. On the other hand, making use of portable devices, such as smartphones and microfluidic paper-based analytical devices, has facilitated on site accurate urine glucose monitoring in real time. All these rapid advancements in nanotechnologies and devices have contributed greatly to the development of cost effective, highly sensitive, user friendly urine glucose biosensors. This review summarizes the most recent improvements in two major types of urine glucose biosensors: the optical- and electrochemical-biosensors. We also discuss the limitations, challenges and perspectives of these biosensors. Finally, we propose future research directions, development trends and potential clinical applications of nanomaterial-based biosensors developed for urine glucose detection.